Surveillance for Zoonotic Pathogens and Inuit Qaujimajatuqangit of Ringed Seals (nattiit) (Pusa hispida) in Frobisher Bay and Eclipse Sound, Nunavut, Canada - Sudlovenick, Enooyaq; Simonee, James; Jones, Megan E.B.; L'Hérault, Vincent; Hernández-Ortiz, Adrián; Jenkins, Emily; Parker, Sarah; Mavrot, Fabien; Schneider, Angie; Kutz, Susan; Saliki, Jeremiah T.; Daoust, Pierre-Yves (The Arctic Institute of North America, 2023)
Ringed seals (Pusa hispida) (nattiq (s.), nattiit (pl.) [Inuktut]) provide an important food staple for Nunavummiut (Indigenous residents of Nunavut). We studied the health of nattiit harvested by hunters from Baffin Island, Nunavut, via Inuit Qaujimajatuqangit and veterinary science. We conducted serological surveys and polymerase chain reaction (PCR) for select zoonotic pathogens, including Brucella spp., Erysipelothrix rhusiopathiae, Leptospira interrogans, and Toxoplasma gondii, in 55 nattiit from Frobisher Bay (FB) and 58 nattiit from Eclipse Sound (ES). We used a digestion assay to determine the presence of Trichinella spp. larvae in muscle samples from these seals. We conducted interviews with nine Local Knowledge Holders (LKHs) from Iqaluit (FB) and nine from Pond Inlet (ES) to gather their observations about nattiq health. The hunters evaluated nattiq health through a combination of behavior, nutritional condition, and appearance of skin and organs. They rarely observed severely ill nattiit. Hunters from ES but not from FB observed declining nattiit population numbers. In both regions, they observed increased numbers of harp seals (Phoca groenlandica). Frequencies of natural exposure among nattiit from FB and ES, based on seroprevalence, were 20.5% and 37% for Brucella spp., 25% and 11% for E. rhusiopathiae, 93% and 100% for L. interrogans, and 10% and 27% for T. gondii, respectively; PCR was negative for these pathogens in organs and tissues of seropositive animals. We did not detect larvae of Trichinella spp. Knowledge and experience from the LKHs in assessing nattiq health, complemented by negative findings from direct detection methods, provide reassurance about the safety of nattiit as country food, despite their exposure to some zoonotic pathogens in their natural environment. Les phoques annelés (Pusa hispida) (nattiq (s.), nattiit (pl.) [en inuktut]) constituent une source de nourriture importante pour les Nunavummiut (habitants autochtones du Nunavut). Nous avons étudié l’état de santé des ...